The Wolf Shall Dwell with the Lamb : permanent installation, Tel Aviv Jaffa - Bartana, Yael (2024)
The sculpture, The Wolf Shall Dwell with the Lamb, is a contemporary adaptation of the prophecy of Isaiah (Chapter 11, Verse 6), installed as a suspended monument to world peace. At first glance, the figures of the wolf and lamb rest together, enveloped in cloth, as if frozen in a moment just before the public unveiling of the sculpture. Yet upon closer inspection, the fabric is revealed as inseparable from the work itself, enshrouding it forever. The sculpture’s form simultaneously embodies a yearning for an idyllic future peace and the impossibility of ever attaining this vision. The dream persists, forever unfulfilled. The veiled image alludes to a utopian destiny even as it questions the very nature of what is to come, contemplating an imagined possibility of the end of history and the triumph of the spirit.
Keywords: sculpture; monument; peace